1969
DOI: 10.1002/anie.196900971
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Activity of Transition Metal Compounds in the Liquid‐Phase Oxidation of Hydrocarbons

Abstract: A and B', and the nepbelauxetic ratio P = B'/Bo of octahedral diethyldithiophosphinato complexes KCzHs)2P(S)Sl&f.BrO < CIO = (C2H&P(S)SG < (CzH50)2P(S)SQ < F O < H20 < NH3 < H2N-(CH&-NH* > CNo whereas its position in the nephelauxetic series is as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…The radical-chain mechanisms proposed in the literature usually stop at this point, [3,5,13] often attributing the formation of the major reaction products, CyOH and Q=O, to the radical termination step (1). However, the long radical chain, of the order of 100, [5] clearly implies that major products can only result from chain-propagation steps.…”
Section: Introductionmentioning
confidence: 99%
“…The radical-chain mechanisms proposed in the literature usually stop at this point, [3,5,13] often attributing the formation of the major reaction products, CyOH and Q=O, to the radical termination step (1). However, the long radical chain, of the order of 100, [5] clearly implies that major products can only result from chain-propagation steps.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The synthesis of cyclohexanone (QO) is of special interest, [2] as it is a key chemical for the production of polyamides such as nylon 6 and nylon 6,6. It is generally recognized that the thermal reaction of CyH with O 2 proceeds via a complex radical chain mechanism, with a limit of 5 % on the conversion to prevent overoxidation of the desired products.…”
mentioning
confidence: 99%
“…Allara and Edelson (1977) denote such phenomena as "inhibition-catalysis switching". Many previous results about the oxidation of hydrogen and hydrocarbons (Marsal-Bonnernaison, 1971;Marsal et al, 1972;Rust and Vaughan, 1949;Babaeva et al, 1959;Knorre et al, 1959;Ingold, 1961;Shlyapnikov et al, 1961;Cullis et al, 1963;Vetchinkina et al, 1967;Emanuel et al, 1969;Smurova et al, 1971;Morrison and Scheller, 1972;Nettleton and Stirling, 1974;Herzberg et al, 1976) revealed either the absence of inhibition or catalysis in the presence of inhibitors, or else inhibition-catalysis switching.…”
Section: Introductionmentioning
confidence: 91%